China Reaches For the Red Planet. - Digregorio, B.E.
The China National Space Administration and the Russian Federal Space Agency (Roscosmos) signed a formal agreement in March that will allow China to send a small satellite called the CDP-I to Martian orbit, piggybacking on the Phobos-Grunt orbiter. According to Alexander Zakharov of the Space Research Institute in Moscow, project scientist for the Phobos-Grunt mission, the CDP-I would test a deep-space tracking system, measure the various constituents of the Martian atmosphere, and study the plasma field around Mars during a one-year period. The Chinese are also contributing a thermal differential analyzer for the gas-chromatograph system, to be used in analyzing the elements contained in soil samples taken from Phobos before they are brought back to Earth. The instrument is being built by the Hong Kong Polytechnic Institute.
Keywords: CDP-I satellite; China National Space Administration; Hong Kong Polytechnic Institute; Martian atmosphere; Martian orbit; Moscow; Phobos-Grunt orbiter; Roscosmos; Russian Federal Space Agency; Space Research Institute; Deep-space tracking system; Gas-chromatograph system; Plasma field; Soil elements; Thermal differential analyzer